FAKTOR-FATOR YANG MEMPENGARUHI WISATAWAN MENGUNJUNGI PANTAI ZAKAT DI KOTA BENGKULU - Huda, Syamsul; Ikhwan, Jalal (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2018)
Syamsul Huda, Jalal Ikhwan; The research aims to determine the number of variables that affect tourists visiting Zakat beach in Bengkulu city. The population used is the visitors who visit Zakat beach. The type of data implemented is the primery daya. The way of implement it is by spreading out of questioners. The research puts on two variables. First, it is the independent variable. It consist of servicing, the trimming of the facilities, safety and earning. Where as the dependent variables focuses on the readability of the visitors to visit Zakat beach. The test stage are done by utilizing spss. To create the hypothesis test stages, it can apply the multiple regression model and t-statistic test. Building upon the hypothesis test result, it has been uncovered that the quality of servicing and safety have significant effects to the readibility of the visitors to come to see Zakat beach in Bengkulu city of Bengkulu province. It can be concluded that the trimming of the facility and earnings do not make significant effects towards the viusitors readability to pay a visit to Zakat beach.Key Words: Service, Facilities, Security and Income.